THE VIRTUE IN CORE VALUES OF BUGINESE CULTURE: A WORLDVIEW FROM PHILOSOPHICAL, RELIGIOUS, AND MORAL PERSPECTIVES - Fathu Rahman; Andi Muhammad Akhmar; Muhammad Hasyim; M. Dalyan; Fakhriawan Fathu Rahman (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
The purpose of this strive study is to reveal the implementation of core values principle of Buginese culture from three perspectives, namely of philosophy, religion, and moral perspective. The Buginese culture belongs to the Bugis people. Bugis people are a community that occupies the area of South Sulawesi alongside the Makassar, Toraja, and Mandar ethnics. They live in harmony and form social systems and institutions. As an ethnic that dominates the population of South Sulawesi, the Bugis ethnic strongly maintains their culture. This can be seen in their principle of core values in the Buginese culture. The core values of Buginese are also a reflection of their worldview in this life. This study aims to uncover 1) the principle of core values of Buginese ethnic through their cultural ideologies, and 2) the aspect of philosophy, religion, and moral perspectives behind their principle of core values. This study utilizes the Cultural Semantics theory with an interpretive qualitative method, which relies on its analysis of the descriptive meaning of expressions. The results of this study indicate that the principle of core values of Buginese culture is awake because they practice the cultural heritage of their ancestors by actualizing it in a contemporary context. The implication of this research is that a cultural-value is maintained when culture has a dynamic aspect to the needs of the cultural.